Effectiveness of D.A.R.E/Keepin' it REAL bullying prevention program among Brazilian students. Issue 2 (6th November 2022) - Ferreira‐Junior, Valdemir; Valente, Juliana Y.; Andreoni, Solange; Sanchez, Zila M.
Abstract: Introduction: Given the growing scientific evidence on the detrimental effects of bullying, several prevention programs have been implemented internationally to prevent this behavior among students. Brazil's Educational Program for Drug and Violence Resistance (PROERD) is an adaptation of US' DARE/Keepin' it REAL program, being the most widespread school‐based prevention program in the country. However, it has been offered without any effectiveness evaluation. As such, this study evaluates the effectiveness of PROERD in reducing bullying perpetration and victimization among students. Methods: Two cluster randomized controlled trials were carried out with 4030 students (1727 5th graders and 2303 7th graders) in 30 public schools in São Paulo, Brazil. The intervention group attended 10 PROERD classes taught by trained police officers whereas the control group underwent no intervention. Data were collected by self‐administered questionnaires using smartphones at two moments (baseline preintervention and 9‐month follow‐up). Multilevel analysis included two paradigms, complete cases (CC) and intention‐to‐treat (ITT), using Full Information Maximum Likelihood (FIML) and Multiple Imputation (MI). Results and conclusion: Results show no statistical difference between groups, indicating lack of evidence on PROERD's effectiveness in preventing bullying behaviors. The insufficient number of classes on bullying prevention and the lack of cultural adaptation may explain these unexpected results. New in‐depth evaluation studies concerning the program's components and process are needed.